THE SUPPRESSION OF TWO ENDOFIT FUNGUS AGAINST PATHOGEN IN GONDANG MANIS JAMAICAN APPLE - ambar, ambar susanti; Afifah, Nur; Febrianti, Ruri (Universitas Islam Balitar, 2021)
This study aims to determine the ability of two endophytic fungi in Gondang Manis jamaican apple to inhibit the development of indigenous pathogenic fungi on these plants. The isolates of Trichoderma sp and Metarhizium sp were obtained from the exploration of endophytic fungi on the tissue of the Gondang Manis jamaican apple plant, while Fusarium sp was the result of exploration on the rhizosphere soil of the plant. Tests were carried out in vitro with a dual culture method using a completely randomized design (CRD) with FT (Fusarium - Trichoderma) and FM (Fusarium - Metarhizium) treatments, each with 5 replications. Determination of the resistance level based on PIRG and Bell Rating. Analysis using ANOVA p (˂0.05) and LSD test (p˃ 0.05). The results showed that Trichoderma sp has a high inhibiting ability (PIRG = 70%; Bell Rating = 2) against Fusarium sp, while Metarhizium sp is considered low (PIRG = 20.5%; Bell rating = 4). This shows that Trichoderma sp. Isolate has a better ability than Metarhizium sp in inhibiting the development of Fusarium sp. The mechanism of inhibition of the pathogen Fusarium sp by Trichoderma sp is to seize nutrients from pathogens Key word : Inhibition, Fusarium sp, Metarhizium sp, Trichoderma sp.